Value-added beef processing: increasing the value of beef shanks using BaaderTM processing technology - Campbell, R.E.; Hunt, Melvin C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Using a BaaderTM desinewing machine on beef shanks can increase the value of a beef carcass by $1 to $5 by improving palatability and texture and reducing fat. By varying belt pressure and drum opening size and passing shanks twice through the desinewer, we obtained commercially acceptable yields. Maximum lean yield was 93% of the shank using 5 mm drum holes for both passes. With 3 mm drum holes, very lean produced on the first pass. Using desinewed lean and flaking the sinew with an Urschel Commitrol®, we produced low-fat (10%) ground beef patties. Patties from desinewed lean alone and/or desinewed lean with flaked sinew reincorporated were more acceptable (P<.05) and had fewer noticeable connective tissue particles than patties made from unprocessed ground shank.
Keywords: Beef; Shanks; Sinew; Collagen low-fat